2016
DOI: 10.1136/bmjopen-2016-011725
|View full text |Cite
|
Sign up to set email alerts
|

Medical professionals' perspectives on prescribed and over-the-counter medicines containing codeine: a cross-sectional study

Abstract: ObjectivesTo explore prescribing practitioners' perspectives on prescribed codeine use, their ability to identify dependence and their options for treatment in the UK.DesignCross-sectional design using a questionnaire containing closed-ended and open-ended items.SettingA nationally representative sample of prescribing professionals working in the UK.Participants300 prescribing professionals working in primary care and pain settings.ResultsParticipants stated that they regularly reviewed patients prescribed cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
2
34
0
Order By: Relevance
“…Patients were thought to be unaware of risk of dependence and safe use of codeine-containing medicines. This was similar to findings reported by practitioners in the UK (25). The indication by prescribing professionals regarding patients' lack of knowledge surrounding their use of codeine medicines is worrying and requires greater exploration.…”
Section: Discussionsupporting
confidence: 78%
“…Patients were thought to be unaware of risk of dependence and safe use of codeine-containing medicines. This was similar to findings reported by practitioners in the UK (25). The indication by prescribing professionals regarding patients' lack of knowledge surrounding their use of codeine medicines is worrying and requires greater exploration.…”
Section: Discussionsupporting
confidence: 78%
“…In both countries, codeine is available as Prescription-only medicines (POM) and as Pharmacy medicines (P) sold 'over-the-counter' in licensed pharmacies without a medical prescription. 12 Prescribed codeine may contain a high dose of codeine (15,30 or 60 mg per unit dose), either alone or in combination with a non-opioid analgesic, such as paracetamol or ibuprofen. The codeine dose in 'over-the-counter' preparations is restricted to lower amounts (maximum 12.8 mg per unit dose).…”
Section: Introductionmentioning
confidence: 99%
“…However, a UK survey of general medical practitioners (GPs) underlined problems relating to both categories: more than half reported that patients lack awareness of the potential harms of prescribed codeine and more than 80% reported that the availability of 'over-the-counter' codeine adds to the potential for misuse. 15 An investigation of codeine use and dependence in the UK and Ireland is timely because of the recent indicators of problems of mortality and dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that such training is needed for a broad range of health professionals, including psychiatrists, pharmacists, and in particular GPs. [4] Best-practice guidelines for the management of opioid use disorders have been developed by SAAMS, [19] but few of the non-medical treatment providers surveyed were aware of them. Furthermore, these guidelines and those from countries such as Australia and New Zealand are not specific to individuals dependent on codeine and tend to focus on stronger opioids such as heroin.…”
Section: Discussionmentioning
confidence: 99%
“…[4] The corresponding percentages for Ireland and South Africa (SA) were 43% and 35%, respectively. [5] As a result, individuals who are misusing or dependent on codeine are increasingly being seen in specialist substance abuse treatment centres.…”
Section: Researchmentioning
confidence: 99%